A Epidemiological Profile of Mycoplasma Hominis and Ureaplasma Urealyticum Mycoplasmas at the University of N’Djamena Teaching Hospital (CHU-R) - Hamit, Mahamat Alio (British Journal of Healthcare and Medical Research, 2022)
Mycoplasmas are very small bacteria without a wall. Mycoplasma hominis and Ureaplasma urealyticum are commensal germs of the urogenital tract, where they are frequently observed without their presence being of a pathological nature. To consider their pathogenicity and express their genitourinary infection, these two species must be isolated at a high concentration. The objective of this study was to determine the role of these two mycoplasmas in human pathology, their resistance to antibiotics and also to better understand these bacteria and to assess their intervention in genital infections. This is a retrospective descriptive and analytical study started from 2017 to 2021 at the laboratory of University Hospital of La Renaissance in N'Djamena (Chad). Analyses of all the records showed that among 342 patients performed Mycoplasma examinations 240 were male with a sex ratio of 2.35 (M/F). Among all the patients, 92 were infected by Mycoplasmas with the prevalence rate of 27%. Analysis of samples from infected patients shows the presence of: U. urealyticum in 68 patients (74%), M. hominis in 10 patients (10.87%) and co-infection of the two species in 14 patients (15.21%). The study confirmed that the most age group infected in this study was the age group [0-25]. The resistance of each positive case was observed in the Mycoplasma IST3 gallery. The strain of U. urealyticum showed the resistance to all molecules. These resistances are less than 20% for floroquinolone Moxifloxacin, and this resistance was greater than 20% for the other molecules. On the other hand, M. hominis was sensitive to Tetracycline and macrolide Telithromycin, although resistance to floroquinolones Levofloxacin and Moxifloxacin was 20% and 80% respectively. In the case of co-infection have presented various resistances to all molecules, the smallest was Levrofloxacin with the prevalence of 21.42%. These variations of resistance justify the interest of identification of these two species and the study their sensitivity for a good management of these infections. Keyword: Mycoplasma, resistance, antibiotic, University Hospital of La Renaissance in N'Djamena (Chad).